Conceptual Model for Mutual (Host-Guest) Authentication of Intangible Cultural Heritage - Khanom, Shahida; Scott, Noel; Kennelly, Millicent; Moyle, Brent (E-Journal of Tourism; Volume 6 Number 2 (September 2019)DO - 10.24922/eot.v6i2.53471, 2019)
The intangible cultural heritage (ICH) of indigenous communities is an attraction to many tourists. Authentic ICH experiences rely on the perceptions and actions of both the host community and guests, a topic which has received with limited scholarly attention, particularly in recent research. This paper presents a conceptual model examining how the mutual (host-guest) authentication of ICH (integrating the perceptions of both hosts and guests) can potentially lead to community empowerment. A literature review has identified that the host community?s attitude and motivation towards ICH, their psychological and economic benefit from ICH, and their participation or involvement in the ICH, together influence the authentication of ICH by these communities. Similarly, a guest?s attitude to and motivation for ICH as well as the way the traditional objects, events or environment are experienced, influence the authentication of ICH. The proposed mutual ICH authentication model combines the interaction of such host and guest factors in authentication of ICH, i.e. both the host community and guest should perceive the same elements as authentic ICH through a synthesis of their own unique perspectives. The perceived authenticity of ICH by the host and guest is reflected in their loyalty, satisfaction, and support for tourism. Further, the model suggests that tourism based on authentic ICH has the potential to empower local communities in their economic, social, psychological and political domains. The proposed model may be useful for future research defining power relations in the authentication of ICH and improving community-based ecotourism through community empowerment. Keywords: intangible cultural heritage, authenticity, mutual authentication, cultural tourism, community empowerment